Financial performance, capital structure, and firm's value: The moderating role of dividend policy - N Rusnaeni; Dani Rahman Hakim; Hari Gursida; Hendro Sasongko (Politeknik Siber Cerdika Internasional, 2023)
This study examines the effect of financial performance and capital structure on firm value with dividend policy as a moderating variable. The sample in this study was 13 property and real estate sector companies from 2011 to 2020, with a total of 130 observations. This study found that financial performance and capital structure positively affect firm value. Meanwhile, this study finds that dividend policy cannot moderate the effect of financial performance and capital structure on firm value. The results of this study indicate that property and real estate investors still prioritize the firm's financial performance. Investors are relatively more cautious in investing in property and real estate sector companies even though the dividends offered are pretty high. Thus, property and real estate sector companies need to be more creative in improving their financial performance and obtaining resources to develop their business.